Non-Ionizing Electromagnetic Fields for Food Safety [Campos Electromagnéticos No Ionizantes Para la Inocuidad Alimentaria] - Ganga-Munoz, M; Godoy-Olivares, L; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2018)
A study was done on the effects and influence of conventional electromagnetic fields (Wifi and Cellular) on contaminating microorganisms. The study was performed using Luria-Bertani (LB) and Water Peptone 2.5% (WP) media in two Wifi band channels (1 and 11) using control samples in each case, for a period of 2 days at -30 dBm. The results show a significant decrease in the viability of Escherichia coli ATCC25922 over WP. However, no significant changes were found when LB was used; both results are repeated for both channels. This generates possible anti-pollution technologies for the food industry using electromagnetic fields as the operating principle. © 2018 Centro de Informacion Tecnologica. All Rights Reserved.